MRTransformer: Transforming Avatar Non-verbal Behavior for Remote MR Collaboration in Incongruent Spaces - Wang, Cheng Yao; Kim, Hyunju; Panda, Payod; Ofek, Eyal; Franco, Mar Gonzalez; Won, Andrea Stevenson (2024 International Symposium on Mixed and Augmented Reality, 2024)
Avatar-mediated remote MR collaboration allows users in different spaces to interact as if they were together. However, directly applying a user's motion to an avatar in incongruent spaces leads to ambiguous and error-prone communication. This paper introduces MRTransformer, a technique enabling dynamic MR collaboration across dissimilar spaces. By adapting transformations to user movements, MRTransformer preserves non-verbal cues and spatial context. It also allows flexible management of collaboration areas and remote object visualization, enhancing remote collaborations. A user study evaluated MRTransformer's effectiveness in preserving non-verbal cues and spatial awareness, and examined social presence and privacy concerns. Findings offer implications for future remote MR collaboration research and design.